2015
DOI: 10.1016/j.jneuroim.2015.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory genes associated with multiple sclerosis: A gene expression study

Abstract: Multiple sclerosis (MS) is an autoimmune inflammatory disease of the central nervous system caused by a complex interaction between multiple genes and environmental factors.HLA region is the strongest susceptibility locus, but recent huge genome-wide association studies identified new susceptibility genes. Among these, BACH2, PTGER4, RGS1 and ZFL36L1 were highlighted. Here, a gene expression analysis revealed that three of them, namely BACH2, PTGER4 and ZFL36L1, are down-regulated in MS patients' blood cells c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 23 publications
(27 reference statements)
1
16
1
Order By: Relevance
“…18 Conversely, BACH2, a critical transcriptional factor regulating the balance between tolerance and immunity by repressing CD4 + T-cell differentiation, 19 is downregulated in pathogenic T cells in EAE mice 18 and in the blood of RR-MS subjects. 20 Our study confirms this observation and extends it to the other MS stages. Very limited information is present in the literature about the expression of other GWAS genes in MS blood cells.…”
Section: Discussionsupporting
confidence: 87%
“…18 Conversely, BACH2, a critical transcriptional factor regulating the balance between tolerance and immunity by repressing CD4 + T-cell differentiation, 19 is downregulated in pathogenic T cells in EAE mice 18 and in the blood of RR-MS subjects. 20 Our study confirms this observation and extends it to the other MS stages. Very limited information is present in the literature about the expression of other GWAS genes in MS blood cells.…”
Section: Discussionsupporting
confidence: 87%
“…Inflammation is another characteristic of these diseases, which involves a group of cytokines, chemokines, and interactions between CD4 + T helper cells (e.g., Th1, Th2, Th9, Th17, and Tfh) and regulatory T cells (Tregs). Gene polymorphisms of the single gene locus encoding Bach2 are also correlated with a variety of immune-mediated diseases including multiple sclerosis (MS) [41], RA [42], CP [20], type 2 chronic airway inflammation [18], inflammatory bowel disease (IBD) [43], and type 1 diabetes [44]. Significantly, both proinflammatory and anti-inflammatory molecular mechanisms are involved in the variant expression of Bach2 and these diseases.…”
Section: The Connection Between Bach2 and Immune-mediated Diseasesmentioning
confidence: 99%
“…TNFAIP3 has been genetically associated with different inflammatory autoimmune diseases (4-7), among which MS (8). We previously demonstrated a significant down-regulation of the TNFAIP3 transcript level in peripheral blood obtained from treatment-naïve MS patients in comparison to HC (9)(10)(11)(12)22). Further researches revealed that the unbalanced expression of TNFAIP3 in MS was mainly due to the monocyte cell population (13).…”
Section: Discussionmentioning
confidence: 97%